Psychological Outcomes in Children and Early Adolescents With Type 1 Diabetes Following Pediatric Diabetes Summer Camp: A 3-Month Follow-Up Study - Troncone, Alda; Chianese, Antonietta; Cascella, Crescenzo; Zanfardino, Angela; Iafusco, Dario (Frontiers in Pediatrics, 2021)
Objective: The aim of this study was to assess general psychosocial adjustment to diabetes and perceived disease management among patients with type 1 diabetes (T1D) and their parents before and after patients’ participation in a diabetes summer camp. Methods: In this follow-up study, 20 children and adolescents with T1D (8 boys; mean age= 11.01 ± .94 years; mean diabetes duration = 3.02 ± 2.27) attending a southern Italian diabetic center, along with their parents, were assessed prior to and 3 months after the youths participated in a 1 week camp-based intervention involving didactic and interactive child-centered education and recreational activities. Patients and their parents completed measures assessing patients’ quality of life and strategies employed by patients to cope with pain. Patients completed also measures evaluating their diabetes psychosocial adjustment, diabetes self-efficacy management, and illness perception; also, their parents completed measures of caregivers’ perceived diabetes burden and treatment satisfaction. Youths’ HbA1c and z-BMI values were also assessed. Within-subjects repeated-measures analyses of variance evaluated pre- and post-camp changes. Results: Camp attendance showed no beneficial effects on glycemic control, as indicated by HbA1c values both before (7.02%) and after (7.28%) camp being lower than 7.5%. HbA1c values were found to have increased after camp (pre-camp= 7.02%, post-camp= 7.28%; p=.010), but since they still fell within an acceptable range, they did not reveal clinically relevant changes in glycemic control. No substantial significant improvement in psychosocial measures was observed in children or parents (all p>.05). According to the parents’ evaluation, social support-seeking as a patient pain-coping strategy was slightly increased (p=.044) after attending the camp. Conclusions: This study does not provide empirical evidence of benefits of participating in a diabetes camp for either patients or their parents. These findings suggest that health care providers rethink such camps as an experience for youths with T1D that actively involves parents and that includes both youth- and parent-focused psychological interventions.